Investigation on the mechanically-induced nanocrystallization in metallic glasses - Ammari, C.; Yousfi, M. A.; Hajlaoui, K.; Georgarakis, Konstantinos (Elsevier, 2020)
Shear-induced nanocrystallization in bent ribbons of Pd40Cu30Ni10P20 metallic glass has been quantitatively investigated via synchrotron radiation. The formed nanocrystals volume fraction during deformation has been directly estimated from X-ray diffraction spectra using peaks area integration. The nanocrystallization process during deformation was found to be strongly linked with the microstructure configuration of shear bands in amorphous alloys. A constitutive model based on free volume approach has been introduced to describe the kinetic of mechanically induced nanocrystallization. The solution of the coupled constitutive equations of the model, fitted to experimental data, permits to determine the physical and mechanical parameters governing the phenomena of shear-induced crystallization in metallic glasses.
Keywords: Activation energy; Free volume; Crystal volume fraction; Deformation-induced nanocrystallization; Metallic glass